Enhancing growth-relevant metabolic pathways of Arthrospira platensis (CYA-1) with gamma irradiation from 60Co. Issue 30 (8th May 2018) - Cheng, Jun; Lu, Hongxiang; Li, Ke; Zhu, Yanxia; Zhou, Junhu
Abstract : Growth-relevant metabolic pathways of Arthrospira enhanced after gamma irradiation. Abstract : The biomass yield of Arthrospira mutant ZJU9000 was 176% higher than that of wild type on day 4, and the results of transcriptome sequencing showed that processes related to cell growth were synergistically enhanced in this mutant. The amount of energy for biomass accumulation increased because the efficiency of the photoreaction was enhanced by the elevated levels of chlorophyll a and carotene. The increased biosynthesis rates of ribose phosphate, nucleotides and multiple vitamins increased the production of genetic materials for cell proliferation. Furthermore, the carbon concentration mechanism in mutant ZJU9000 was enhanced, indicating the increased utilization efficiency of CO2 at low concentration (0.04 vol% in air). The enhancement of these growth-relevant metabolic pathways contributed to the robust growth of Arthrospira mutant ZJU9000.